Whistle-blower Protection through Right to Information: A Critical Review with Special Reference to Sri Lanka - Madushan, G.P.D.; Thilakarathna, K.A.A.N. (University of Colombo, 2022)
Whistleblowing can be identified as a means of voicing out wrongdoings in a given establishment to either inside or outside channels. It should also be noted that whistleblowing is a way of expressing ones dissent concerning a wrongdoing which should be respected and guaranteed, albeit with such limitations as required in a democratic society. While this can be identified as a means of combating corruption and enhancing accountability, transparency and good governance through such disclosures, the existing legal regime in Sri Lanka does not provide explicit protection for such individuals when they are being retaliated against. This research aims to analyse the right to information regime in protecting the whistle-blowers through the right to information law, through a qualitative method by analysing statutory provisions and decisions of the Right to Information Commission of Sri Lanka. The results reveal that section 40 of the Right to Information Act No. 12 of 2016 provides protection for officers and employees of public authorities who disclose or release information which is under their custody, control or possession that they are entitled to disclose under RTI Act should not be retaliated by means of disciplinary action or any punishment. It is argued that this provision is capable of providing some protection for individuals in the public authorities who decide to blow the whistle by a way of disclosing, or releasing upon their own initiation. It is recommended that; whistle-blower protection should be widely recognized in order to achieve the objectives of the Act.
Keywords: Whistleblowing; Right to Information; Release of Information; Transparency; Whistle-blower Protection